Caravanserais and the Silk Road system in Azerbaijan: from Medieval trade infrastructure to contemporary geopolitical networks - Mustafayev, M.M. (Turkic Studies Journal, 2026)
This article examines the historical evolution, architectural typology, and geopolitical significance of medieval caravanserais located along the Azerbaijani segment of the Silk Road. Investigating Azerbaijan’s strategic transit position from antiquity to the modern era, the research demonstrates that caravanserais functioned as complex socioeconomic, cultural, and administrative hubs that structured longdistance trade across Eurasia rather than merely as resting stations. This study is based on archaeological evidence, written sources from Islamic geography, numismatic materials, and architectural analyses of surviving monuments. The earliest traces of caravanserai-type structures in Azerbaijan date back to the 6th–3rd millennia BCE. However, this architectural tradition did not reach its peak until the medieval period under Turkic political entities. The article focuses on the interregional roles of the Bukhara and Multani caravanserais in the Icherisheher (Baku’s Old City). These caravanserais served merchants from Central Asia and India, respectively, and their foundations reveal continuity with earlier urban infrastructure. The article analyzes the transit significance of the Sangachal and Garachi (Miachik) complexes along the Caspian coastal route in terms of their architectural characteristics and function within the broader Silk Road landscape. The Maragheh Observatory, founded in the 13th century, is evaluated as a center of intellectual exchange where scholars from China, India, and Syria collaborated. This illustrates the civilizational dimension of the Silk Road, which extended beyond commerce. Additionally, the article explores the architectural similarities between Azerbaijani caravanserais and monuments in Central Asia and Anatolia. Notable examples include Sultan Han in Turkey and Rabat-i Malik in Uzbekistan. These similarities demonstrate the transnational spread of Turkic architectural engineering under the Seljuk, Timurid, and Safavid empires. The article also emphasizes the role of state patronage, particularly that of the Shirvanshahs and Shah Abbas I, in shaping the caravanserai network as an instrument of trade diplomacy. Additionally, the research addresses how the Silk Road routes changed after the geographical discoveries of the late-15th century and the subsequent growth of the Volga–Caspian corridor. In the contemporary context, the study explores the connection between medieval heritage and modern geopolitical realities by examining the TRACECA transport program, the "Virtual Silk Road" initiative, and the strategic importance of the Zangezur Corridor. Ultimately, the article concludes that Azerbaijan’s caravanserai heritage is a universal architectural legacy and living cultural and strategic resource for regional cooperation among Turkic states.